2007
DOI: 10.1007/bf03022314
|View full text |Cite
|
Sign up to set email alerts
|

Milrinone enhances systolic, but not diastolic function during coronary artery bypass grafting surgery

Abstract: Purpose:To evaluate the effect of milrinone on diastolic function during coronary artery bypass grafting surgery (CABG). Methods:Fifty patients undergoing CABG were randomized to receive a bolus and infusion of milrinone or placebo before cardiopulmonary bypass (CPB) until skin closure. Hemodynamic and transesophageal echocardiographic measurements of systolic and diastolic function were obtained. Pulsed wave Doppler measurements of the early (E wave) and atrial components (A wave) of the transmitral (TMF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
1
42
1
Order By: Relevance
“…21,22 For patients with pulmonary hypertension, pulmonary vasodilators have been shown to improve outcomes. 23,24 For the restrictive LV, milrinone has had mixed results 25,26 whereas close monitoring and optimization of volume status and filling pressures remains the mainstay.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 For patients with pulmonary hypertension, pulmonary vasodilators have been shown to improve outcomes. 23,24 For the restrictive LV, milrinone has had mixed results 25,26 whereas close monitoring and optimization of volume status and filling pressures remains the mainstay.…”
Section: Discussionmentioning
confidence: 99%
“…1 Studies have suggested that intravenous milrinone may be beneficial in the treatment of PH in cardiac surgery. 2,3 Nevertheless, intravenous milrinone has been associated with systemic hypotension 4 and increased vasoactive drug requirements 5 as well as increased morbidity 6 and mortality after cardiac surgery. 7 The use of inhaled milrinone (iMil) has been described in several animal 8,9 and human reports.…”
Section: Résumémentioning
confidence: 99%
“…Characteristics of the study population and the awake population Individual data sets were obtained from 304 patients in seven published studies (3,(14)(15)(16)(17)(18)(19) and from 85 patients in one unpublished study (Table 1). In all studies, LV EDA and ESA were measured using manual planimetry of the endocardial boarders at end-diastole and end-systole according to the guidelines provided by Lang et al (21).…”
Section: Resultsmentioning
confidence: 99%
“…This is individual-level data analysis including data from several published studies (3,(14)(15)(16)(17)(18)(19). All patient data from studies included in this analysis were approved by the local institutional review boards, and written informed consent was obtained from all included patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation